2008
DOI: 10.1080/08860220802212908
|View full text |Cite
|
Sign up to set email alerts
|

Hemodialysis-Induced Left Ventricular Dysfunction Is Associated with an Increase in Ventricular Arrhythmias

Abstract: Conventional hemodialysis results in intradialytic cardiac ischemia in a significant proportion of patients. Segmental myocardial ischemia results in the development of left ventricular regional wall motion abnormalities. Sudden death is the most common cause of mortality in hemodialysis patients. This study looked to examine any association between the development of left ventricular regional wall motion and cardiac arrhythmias. Forty established hemodialysis patients had 24-hour Holter recordings, which comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
85
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(86 citation statements)
references
References 28 publications
1
85
0
Order By: Relevance
“…Data from the present study 1) provide a current estimate of CHX contamination in commercially available IV bags and EC circuits and 2) clearly indicate that the effects of 210 g/l IV CHX (a concentration that conservatively approximates clinical exposure for EC patients) mirror the cardiovascular morbidities associated with EC: bradycardia/dysrhythmia (1,4,5,19,33,38), depressed ventricular contractility (1,2,4,5,8,11,18,19,24,33,38,39,41), low cardiac output (7,11,14,28,31), high systemic and pulmonary vascular resistance (7, 13, 18, 29 -31), hypotension/labile blood pressure (2,7,21), pulmonary hypertension (7, 29 -31), impaired neurological (baroreflex) function (3,5,34,38,39), and edema formation (20,32,39).…”
Section: Discussionmentioning
confidence: 99%
“…Data from the present study 1) provide a current estimate of CHX contamination in commercially available IV bags and EC circuits and 2) clearly indicate that the effects of 210 g/l IV CHX (a concentration that conservatively approximates clinical exposure for EC patients) mirror the cardiovascular morbidities associated with EC: bradycardia/dysrhythmia (1,4,5,19,33,38), depressed ventricular contractility (1,2,4,5,8,11,18,19,24,33,38,39,41), low cardiac output (7,11,14,28,31), high systemic and pulmonary vascular resistance (7, 13, 18, 29 -31), hypotension/labile blood pressure (2,7,21), pulmonary hypertension (7, 29 -31), impaired neurological (baroreflex) function (3,5,34,38,39), and edema formation (20,32,39).…”
Section: Discussionmentioning
confidence: 99%
“…We found no significant association between these aforementioned risk factors and the severity of myocardial stunning, possibly because cardiorenal performance is influenced by a number of humoral and genetic factors (26) that act collectively to exert an effect but in isolation, particularly in pediatrics, are too small to be detectable from our sample size. The major determinant of intradialytic BP is cardiac output and end diastolic volume (27), but clearly regional LV function is important as evidenced by reports of reduced hemodynamic stability in patients developing myocardial stunning despite below average UF volumes (13). Shoji et al (28) found BP reduction during dialysis and not hypertension in adult HD patients as a factor that influenced survival negatively.…”
Section: Discussionmentioning
confidence: 99%
“…Hibernation in turn contributes to congestive heart failure (11) and has been shown to be marker of poor prognosis (12). Within the renal HD cohort, transient myocardial ischemia precipitated cardiac arrhythmias (13), regional fixed systolic dysfunction, and reduced overall systolic function (2).…”
mentioning
confidence: 99%
“…Another two types of arrhythmia, the complex ventricular arrhythmia and premature ventricular complexes, in particular increase the mortality and morbidity. Complex ventricular arrs (those defined as having a Lown score of 3 and more) prevail at a rate of 35% in the HD patient group (Burton et al,2008).…”
Section: Arrhythmiasmentioning
confidence: 99%